Komunitas Belajar dalam Lesson study untuk Memberdayakan Kognitif dan Psikomotor Siswa pada Pembelajaran Biologi di Luar Kelas - Zukmadini, Alif Yanuar; Lestari, Puji; Rochman, Syaiful; Karyadi, Bhakti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to enhance cognitive and psychomotor abilities through outdoor learning, designed and evaluated collaboratively by the learning community within the framework of the Lesson study. The study was conducted on grade X students of MAN Insan Cendekia Bengkulu Tengah. Lesson study was carried out in two cycles, each consisting of the plan, do, and see stages. The